The Effectiveness of Student Facilitator and Explaining Learning Model Assisted by Edmodo to Enhanced Students' Problem Solving Ability - Aulia, Hanis; Savitri, Erna Noor (Universitas Negeri Semarang, 2021)
This study aims to determine the effect and effectiveness of the Student Facilitator and Explaining (SFAE) learning model assisted by Edmodo to enhanced students’ problem solving abilities. This study uses a quasi-experimental research method. The sample in this study was taken by cluster random sampling technique. Data collection techniques in this study used interviews, tests, and questionnaires. Analysis of the influence and effectiveness of the Student Facilitator and Explaining (SFAE) learning model assisted by Edmodo using N-gain analysis and comparative t-test related analysis. The results of the N-gain analysis showed that there was an increase in problem solving ability in the experimental class by 0,45 and in the control class by 0,20. The results of the comparative t-test related showed that there was a significant difference between the problem solving abilities of the control class and the experimental class with t count (3.97) > t tabel (2,0003). The results of the student response questionnaire after carrying out learning with the Student Facilitator and Explaining (SFAE) learning model assisted by Edmodo showed a very good response of 88.4%. The results showed that the Student Facilitator and Explaining (SFAE) learning model assisted by Edmodo was effective in enhanced students' problem solving abilities.